Questioning Social Expectation towards Masculinity in Cloud 9 by Caryl Churchill - Khalilah Aisyah Maharani (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines the depiction of masculinity and its resistance in Caryl Churchill's play Cloud 9 (1979). Social expectations rooted in patriarchal culture enforce rigid standards of masculinity from childhood, suppressing authentic identities to maintain gender conformity. Therefore, this research aims to 1) To identify how the masculine actions in the play differ from the expectations of the Victorian period and 2) To explore how these "different" versions of masculinity challenge traditional social standards and criticize patriarchal power. This study applies qualitative textual analysis and Lucy Nicholas and Christine Agius's theory of Global Masculinism as the basis of analysis with other supporting theories. The findings reveal that masculinity in Cloud 9 is not fixed or natural but constructed by society sustained through physical competence and emotional restraint. This play further demonstrates that it is the acts of resistance from characters that expose the fragility of masculinity. This study contributes to the study of gender and drama by offering new insights into how theatre can critique the persistence and adaptability of masculinist ideologies in the Victorian era.